THE CONTENT PHYSICAL ACTIVITY IN THE CURRICULAR REFERENCE OF THE MATO GROSSO DO SUL STATE OF EDUCATION NETWORK: CONCEPTUAL DISCUSSION AND CRITICAL APPRAISALS ABOUT THE THEME (Fiep Bulletin - online, 2017)
In this article, we will seek to question the use of the concept of "physical activity" present in the Curricular Frameworkof the State Educational Network of Mato Grosso do Sul - High School and Fundamental. For this purpose, the specializedbibliography in the area that covers in a conceptual way the terms "physical activity" and "physical exercise", as well as themisuse of terms used by the media in general, was used as a source of discussion. The purpose of this study is to triangulate theinformation between theory and common sense by investigating possible misunderstandings and implications related to theinappropriate use of the term and its implications within the educational context. Therefore, the concept of physical exercise ispresented as an alternative to remedy the problem.
Keywords: Physical Activity; School content; Curricular Framework of the State Teaching Network of Mato Grosso do Sul High School and Fundamental.